2017
DOI: 10.1038/bmt.2017.120
|View full text |Cite|
|
Sign up to set email alerts
|

Regional intra-arterial steroid treatment in 120 patients with steroid-resistant or -dependent GvHD

Abstract: GvHD results in death in the majority of steroid-resistant patients. This report assesses the safety and efficacy of two regional intra-arterial steroid (IAS) treatment protocols in the largest published cohort of patients with resistant/dependent hepatic and/or gastrointestinal GvHD, as well as identification of predictors of response to IAS and survival. One hundred and twenty patients with hepatic, gastrointestinal GvHD or both were given IAS. Gastrointestinal initial response (IR) and complete response (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…To date, aberrant regulation of the JAK1/2-STAT6 pathway has been identified in different pathological conditions [9] and activated STAT6 has been found in patient samples isolated from Hodgkin lymphomas [10,11], cutaneous T cell lymphomas [12], adult T cell leukemia and B-lymphomas [13,14]. In this article we functionally validated JAK2 Y1007-1008 as a new therapeutic target to reverse therapy resistance by in vitro treatment with ruxolitinib, an already FDA approved JAK1/2 inhibitor [15,16] that is currently also being evaluated for the treatment of B-ALL (NCT02723994) [17], alone or in combination with dexamethasone, in cell lines and in one T-LBL pediatric primary sample. Moreover, our findings also revealed that in these cells STAT6 controls the transcriptional activity of the glucocorticoid receptor (GR) through the binding of GR itself and the inhibition of its activity, which contributes to increasing glucocorticoid (GC) resistance.…”
Section: Introductionmentioning
confidence: 84%
“…To date, aberrant regulation of the JAK1/2-STAT6 pathway has been identified in different pathological conditions [9] and activated STAT6 has been found in patient samples isolated from Hodgkin lymphomas [10,11], cutaneous T cell lymphomas [12], adult T cell leukemia and B-lymphomas [13,14]. In this article we functionally validated JAK2 Y1007-1008 as a new therapeutic target to reverse therapy resistance by in vitro treatment with ruxolitinib, an already FDA approved JAK1/2 inhibitor [15,16] that is currently also being evaluated for the treatment of B-ALL (NCT02723994) [17], alone or in combination with dexamethasone, in cell lines and in one T-LBL pediatric primary sample. Moreover, our findings also revealed that in these cells STAT6 controls the transcriptional activity of the glucocorticoid receptor (GR) through the binding of GR itself and the inhibition of its activity, which contributes to increasing glucocorticoid (GC) resistance.…”
Section: Introductionmentioning
confidence: 84%
“…The OR/CR of GI GVHD was 67.9% and 47.6%, whereas the hepatic OR/CR was 54.9% and 33.3%, respectively. However, its routine use may be limited by the complications associated with arterial catheterization, such as arterial rupture, dissection or thrombosis, temporary arterial spasm, groin haematoma or cellulitis and, rarely, renal failure [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraarterial methylprednisolone administration has shown promise as a potential salvage therapy in steroid-resistant acute GVHD in adults [ 9 , 10 , 11 ]. While one study included an unknown number of pediatric patients [ 19 ], this technique has not been reported in a pediatric cohort of patients outside selective case reports. Understanding the feasibility and efficacy of intraarterial steroid treatment for acute GVHD in children is important because this population suffers from a higher incidence of severe GVHD following SCT and is more likely to experience complications from systemic steroid administration [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%